The Effects of Sertraline on Psychopathic Traits - Dunlop, Boadie W. (2011)
OBJECTIVE: To evaluate whether antidepressants alter expression of psychopathic personality traits in patients with major depressive disorder (MDD). METHODS: Data were collected from a double-blind, placebo-controlled 8-week trial evaluating the efficacy of sertraline (50-200 mg/d) combined with either tri-iodothyronine (T3) or matching placebo in adult outpatients with MDD. Administration of sertraline was open-label; T3/placebo was double-blind. At the baseline and week 8 visits, patients completed the short form of the Psychopathic Personality Inventory (PPI), a well-validated self-report measure assessing two major factors of psychopathy: Fearless Dominance (PPI-1) and Self-centered Impulsivity (PPI-2). Change in PPI scores were assessed using paired t-tests for all subjects who completed a baseline and post-randomization PPI. RESULTS: Ninety patients (84 completers and 6 who terminated the trial early) were eligible for the analysis. Both PPI factors changed significantly from baseline to endpoint, but in opposing directions. The mean score on PPI-1 increased significantly during treatment; this change was weakly correlated with change in depression scores. In contrast, the mean score on PPI-2 decreased significantly, but these changes were not correlated with changes in depression scores. CONCLUSION: Independent of their effects on depression, antidepressants increase adaptive traits traditionally observed in psychopathic individuals, such as social charm and interpersonal and physical boldness. Antidepressants reduce other, more maladaptive, traits associated with psychopathy, including dysregulated impulsivity and externalization.